Significance of Modified Hodge Test in Carbapenemase Detection: A Brief Insight: Modified Hodge Test in Carbapenemase - Ishfaq, Romah; Javaid, Asghar; Naz, Aneeqa; Zulfiqar, Atif; Javed, Muhammad Shahid; Javeed, Mehvish (Pakistan Journal of Health Sciences, 2024)
Neonatal sepsis is one of the leading causes of neonatal deaths. A. baumannii-calcoaceticus is the most notorious bacterial agent. Carbapenems are the most important antibiotics and modified Hodge Test is considered as important phenotypic method for observing Carbapenemase production. Objective: To evaluate the efficacy rate of Modified Hodge Test, for detection of Carbapenem resistance. Methods: A cross sectional study was conducted at department of pathology, Nishtar Medical University, Multan from August 2023 to September 2023. The blood samples of suspected cases of sepsis were collected and after isolation of Acinetobacter baumannii sensitivity of multiple antibiotics were checked by disc diffusion method. Carbapenem resistance was re-evaluated by Modified Hodge Test using Meropenem disc (10 µg). All data were entered and analyzed by SPSS version 23.0. Results: Total samples of neonatal sepsis were 182. 83 (45.6%) were culture positive for bacterial growth. Among the positive samples 26 (31.3%) were isolated as Acinetobacter baumannii. Kirby-Bauer disc diffusion method was used to check sensitivity of multiple antibiotics including Carbapenems. Out of 26 Acinetobacter isolated samples, 16 were found to be Carbapenem resistant by this method. Modified Hodge test was used to re-confirm Carbapenem resistance. Out of 16 Meropenem resistant cases this phenotypic test only detected 5 cases (31.25%). Conclusions: Staphylococcus aureus followed by Acinetobacter baumannii were isolated predominantly and Carbapenem resistance has markedly increased. In contrast to a study conducted in 2010 in Pakistan on MHT effectiveness where effectiveness of MHT for Carbapenemase detection was satisfactory, our results reveled that some other techniques should be introduced for Carbapenemase detection as Modified Hodge test did not give satisfactory results